Effectiveness of design thinking pedagogy in SCCT-based career guidance: Students’ career decision-making self-efficacy and perceived value - Yahong Cai; Nalini Arumugam; Yukai Chen (PLoS ONE, 2026)
This study investigates the impact of design thinking pedagogy on college students’ career decision-making self-efficacy and perceived value in career education. A quasi-experimental design was employed with 140 participants from two homogeneous intact groups. The experimental group implemented design thinking pedagogy, whereas the control group received the regular teacher-centered method in career guidance courses. Data were collected using mixed methods. Quantitative data were collected using a career decision-making self-efficacy scale, and qualitative data were obtained through semi-structured interviews to explore students’ perceived value. Data were analyzed using independent samples t tests, analysis of covariance, and thematic analysis. The results revealed that design thinking pedagogy significantly improved students’ career decision-making self-efficacy through practical skill acquisition, emotional empowerment, and social identity, and perceived high evaluation, indicating that design thinking pedagogy is effective in career education. This study provides empirical evidence for integrating design thinking into career education, contributing to innovative pedagogies in higher education and emphasizing its importance in preparing students to proactively navigate evolving profession landscapes.